The Effect of Income, Product Knowledge, Trust, and Promotion on Public Interest in Using Sharia Pawn Services. - Hidayat, Muhammad Shamil; Mansah, Adi (Universitas Trunojoyo Madura, 2025)
The growing demand for ethical and interest-free financial services in Indonesia has raised questions regarding the factors that drive public interest in Islamic pawnshops (rahn). Although conventional pawn services remain dominant, previous research has shown inconsistencies in identifying the most influential drivers of customer interest. This study aims to fill that gap by examining the combined effects of income, product knowledge, trust, and promotion on the interest in using sharia-compliant pawn services, specifically in South Jakarta—a region with increasing awareness of Islamic finance.A quantitative method with a causal research design was employed, targeting 130 respondents through purposive sampling. Participants included former users of sharia pawn services, conventional users open to Islamic alternatives, and individuals interested in Islamic pawn offerings. Data collection was conducted using structured questionnaires, and analysis was performed through Structural Equation Modeling (SEM) using SmartPLS.The findings indicate that all independent variables significantly and positively influence customer interest, with the model explaining 80.5% of the variance. Promotion showed the strongest individual impact (p = 0.000), followed by trust (p = 0.008), income (p = 0.014), and product knowledge (p = 0.010). These results underline the importance of targeted promotion, customer trust, income stability, and education on sharia products in enhancing public engagement with Islamic pawn services.